Analyse De La Variabilite Hydroclimatique Et Impacts Des Barrages Sur Le Regime Hydrologique D’une Riviere De Zone Semi-Aride : Le Sebou Au Maroc - Eudes, Bahin Yoli Baudet; Souad, Haida; Jean-Luc, Probst (European Scientific Journal, ESJ, 2017)
The analysis and characterization of hydroclimatic variability over a long period of time is fundamental for understanding the impacts of climate change and vulnerability of hydrological regimes. The present work is a study of the spatial and temporal variability of the climatic and hydrological series in the Sebou river basin (Morocco) over the past sixty years using Hanning low-pass filter of second order and statistical tests of stationarity of climate and hydrological time series. These statistic testing methods were applied to analyze the spatial and temporal evolution to the hydroclimatologic data of the AzibEsSoltane, M'jara and MechraBelKsiri hydrometric stations, which are, respectively, located in the Middle Sebou, the Ouerrha Tributary of the Sebou and the Low Sebou. This analysis shows that climate variability has resulted particularly in strong interannual fluctuations in rainfall reflected by a succession of dry and wet periods between 1939 and 1979 and a general decrease in precipitation since 1980. The Water flow time series analysis are marked by ruptures detected mainly between 1972 and 1978 reflecting rainoff declines of about 50% in the Sebou downstream and 70% in the middle Sebou. Several decreases in water discharge (up to 90%) were also detected in the Ouerrhariver since 1996, when the Al Wahda dam started operating.The analysis of the relationships between rainfall and water discharge shows that the impacts of dams constructions are stronger than the climatic effect in the Ouerrha river. The results of this study are important indicators for the assessment of combined climate risks.